Cognitive Processes of Using Representational Form in Mathematical Modeling Based on Gender Differences - Elika Kurniadi; Novita Sari; Darmawijoyo Darmawijoyo (Jurnal Elemen, 2021)
The process of thinking in formulating a mathematical model requires cognitive processes. In learning mathematics, one of the factors that influence mathematics ability is gender differences.  This research explores and provides an overview of the cognitive processes, especially using the representational form in mathematical modeling regarding gender differences. The type of research used is descriptive exploratory with a qualitative approach. The research subjects were 36 pre-service teachers in the mathematics education study program, consists of 18 males and 18 females. The instruments were a written test and an interview guide sheet. The result shows that males get higher percentages than females to answer the representational problem correctly. In conclusion, both males and females solve the graph problem using representative form through three components of the cognitive process.  The first and second component, namely knowing and applying, shows the same behavior: retrieving the information from the mathematical problem and displaying the information into the graph. For the third component, reasoning also offers the same behavior because the truth of the graph that justifies refers to the mathematical properties. The study implies that it might be the same treatment for males and females to improve representational form regarding the components of cognitive process, namely, knowing, applying, and reasoning.